Mengenal Instrumen Investasi Bagi Para Pelaku Umkm Binaan Rumah BUMN Yogyakarta - Pramayuda, Agung; Musadat, Irfan Achmad; Ningrum, Retno Widya (Abdimas Galuh, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are a crucial pillar in Indonesia’s economy. MSMEs not only drive local economic growth but also serve as a source of innovation and national economic resilience. Amid increasingly complex economic dynamics and intense business competition, MSMEs are required to adapt and develop effective financial management strategies to survive and grow. One important aspect of financial management for MSME owners is understanding investment instruments. Investment is a way to increase asset value and strengthen business capital. However, many MSME owners are still unfamiliar with the various investment instruments available, along with the benefits and risks associated with them. This lack of knowledge can hinder MSMEs’ ability to optimize their financial resources for long-term business development. in implementing this activity, the team followed several stages: the Lecture Method, where speakers were given time to present material on online loan management, and the Q&A Method, which was used after the lecture to give participants the opportunity to further explore the material presented. One of the challenges faced by MSMEs in Rumah BUMN Yogyakarta is the lack of financial literacy. This results in suboptimal management of business funds and the inability to make sound financial decisions. The community service activities carried out by Rumah BUMN Yogyakarta, with support from the Indonesia Stock Exchange (IDX) Yogyakarta Representative Office, have had a significant impact on improving MSMEs’ understanding of investment instruments and financial management.